Anaerobic breviate protist survival in microcosms depends on microbiome metabolic function. - Aguilera Campos, Karla Iveth; Boisard, Julie; Törnblom, Viktor; Stairs, Courtney (Lund University, 2025)
Additional data associated with the article "Anaerobic breviate protist survival in microcosms depends on microbiome metabolic function." (see preprint under "Related Material").

ABSTRACT
Anoxic and hypoxic environments serve as habitats for diverse microorganisms, including unicellular eukaryotes (protists) and prokaryotes. To thrive in low-oxygen environments, protists and prokaryotes often establish specialized metabolic cross-feeding associations, such as syntrophy, with other microorganisms. Previous studies show that the breviate protist Lenisia limosa engages in a mutualistic association with a denitrifying Arcobacter bacterium based on hydrogen exchange. Here, we investigate if the ability to form metabolic interactions is conserved in other breviates by studying five diverse breviate microcosms and their associated bacteria. We show that five laboratory microcosms of marine breviates live with multiple hydrogen-consuming prokaryotes that are predicted to have different preferences for terminal electron acceptors using genome-resolved metagenomics. Growth of the protists within the microcosms respond differently to electron acceptors depending on the make-up of the prokaryotic community. We find that the metabolic capabilities of the bacteria and not their taxonomic affiliations determine protist growth and survival and present new potential protist-interacting bacteria from the Arcobacteraceae, Desulfovibrioaceae and Terasakiella lineages. This investigation uncovers potential nitrogen and sulfur cycling pathways within these bacterial populations, hinting at their roles in syntrophic interactions with the protists via hydrogen exchange.


Files included:

- 16S_Breviate_Associated_Trees - 16S rRNA phylogenetic trees for breviate-associated bacteria, including alignments, IQ-TREE outputs, and colorized tree visualizations.
- 18S_Breviate_Associated_Trees - 18S rRNA sequences from multiple sources, alignments processed with SSU-align and SSU-mask, and phylogenetic trees generated using IQ-TREE.
- Arcobacter_EP1_Annotation - Gene prediction and annotation of Arcobacter sp. EP1 (GCA_001655195.1) using Prokka.
- DIC_breviates - Differential interference contrast (DIC) microscopy images of breviates.
- FlowCam_classified_images - classified FlowCam generated images, used for evaluating breviate concentrations.
- FISH_breviate_microscosm - Fluorescence in situ hybridization (FISH) images of breviate microscosms.
- FISH_interaction_percentages - FISH raw photos used to estimate the number of bacterial cells with FISH signal that interacted with the breviate cells.
- GTDBtk_Classification_and_Phylogeny - GTDB-tk classification and phylogenetic placement of Arcobacteraceae, Desulfovibrionaceae, and Terasakiella genomes.
- Metagenomic_MAGs - Metagenome-assembled genomes (MAGs) generated through anvi’o binning and reassembled using Trycycler, with taxonomic classification, metabolic annotation, and quality assessment.
Each compressed directory includes a README file describing its contents in detail. Additionally, a general README and manifest file are also included in this repository for navigation and reuse.
Keywords: Evolutionary ecology; Microbial ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi